Tinjauan Hukum Terhadap Pelaksanaan Hak Asasi Manusia Dan Pemberdayaan Perempuan: Kabupaten Lumajang - Muchamad Taufiq; M. Wimbo Wiyono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
That Human Rights are fundamental rights inherent in human beings by nature, universal and timeless as the grace of God Almighty cover for life, family rights, the right to develop themselves, the right of justice, freedom, the right to communicate, right to security and rights welfare and therefore should not be ignored or taken away by anyone. " Similarly, Lumajang Government Policy on the implementation of Human Rights and Empowerment of Women has been in accordance with the mandate of Law Number 39 Year 1999 on Human Rights has issued Regional Regulation No. 37 of 2007 regarding the Organizational Structure and Administration of the Office of Community Empowerment Lumajang Lumajang conjunction with the decree No. 37 of 2008 on the translation task and function of the Organization Department of Community Empowerment Lumajang. And also Enforcement of Human Rights and Empowerment of Women in Lumajang was based on the Law of the Republic of Indonesia Number 26 Year 2000 on Human Rights Court in particular Chapter V of the Obligations and Responsibilities of the Government and the Law of the Republic of Indonesia Number 32 Year 2004 on Government area. Similarly, Implementation and Enforcement of Human Rights of Women Empowerment has been implemented by the Office of Women's Empowerment Lumajang been going well as the programs of activities that have been carried out through seven program areas of empowerment of women.